Rankings, accreditations, and international exchange students - Gabriele Marconi (IZA Journal of European Labor Studies, 2013)
Do international university rankings or professional accreditations affect the preferences of exchange students over different institutions? This paper investigates the question by analysing the determinants of Maastricht University School of Business and Economics (SBE) students' choices of possible destinations for their compulsory period of study abroad. The unique dataset used includes 2,970 applications for studying abroad between academic years 2004/2005 and 2008/2009, and 152 partner institutions across the world among which students can choose. A model is developed and estimated by means of the probit model. The results indicate that international rankings (the THESR) and business school accreditations (AACSB and EQUIS) are important for exchange students with high academic achievement, even after taking university fixed-effects into account. However, the estimated effect is small or even negative for students with lower academic achievement. As suggested by previous literature, also other characteristics of the university location (e.g. distance from the equator) affect students' choices.
Keywords: I23; C35; 330; International students; Higher education institutions; Rankings; Accreditations; Student choice